Biceps tenotomy or tenodesis in association with rotator cuff repair: is there an influence on functional results? A retrospective cohort study - Malavolta, Eduardo Angeli; Sousa, Alana Caselato de; Gracitelli, Mauro Emilio Conforto; Assunção, Jorge Henrique; Silva, Fernando Brandão de Andrade e; Ferreira Neto, Arnaldo Amado (São Paulo Medical Journal, 2022)
BACKGROUND: Instability or tears of the long head of the biceps tendon (LHBT) may be present in more than 35% of rotator cuff repairs (RCR). OBJECTIVE: To compare clinical results from patients undergoing arthroscopic RCR, according to the procedure performed at the LHBT. DESIGN AND SETTING: Retrospective cohort study designed at the shoulder and elbow clinic of Instituto de Ortopedia e Traumatologia, Hospital das Clinicas, Faculdade de Medicina, Universidade de Sao Paulo, Brazil. METHODS: Functional results among patients were compared using the American Shoulder and Elbow Surgeons (ASES) and University of California Los Angeles (UCLA) scales, according to the LHBT approach adopted: no procedure, tenotomy or tenodesis. RESULTS: We evaluated 306 shoulders (289 patients): 133 underwent no procedure at the LHBT, 77 tenotomy and 96 tenodesis. The ASES scale at 24 months showed no difference (P = 0.566) between the groups without LHBT procedure (median 90.0; interquartile range, IQR 29), tenotomy (median 90.0; IQR 32.1) or tenodesis (median 94.4; IQR 22.7); nor did the UCLA scale (median 33; IQR 7 versus median 31; IQR 8 versus median 33; IQR 5, respectively, P = 0.054). The groups differed in the preoperative functional assessment according to the ASES and UCLA scale, such that the tenodesis group started from higher values. However, there was no difference in pre and postoperative scores between the groups. CONCLUSION: Tenodesis or tenotomy of the LHBT, in the sample analyzed, did not influence the clinical results from RCR, as assessed using the ASES and UCLA scales.